Prinsip-prinsip komunikasi pustakawan (persfektif komunikasi Islam) - khatibah khatibah (UIN Sumatera Utara, 2016)
AbstractsThis article discusses principles of communication of librarians (perspective of islamic communication).It takes effort, thought and the ability of librarians to keep doing excellent service to users. Excellent service required good communication skills. In the qur'an has good and right of the concept of communication in accordance with the duties and responsibilities of librarians in serving users.